Aplicación del proceso de atención de enfermería en paciente de 6 años con meningitis, en el área de hospitalización pediátrica en el Hospital Universitario de Guayaquil - Engracia Bravo, Stefany Noely (2020)
The clinical case presented below is about a child patient with meningitis, through it it is informatively sought to raise awareness among all readers to prevent this type of pathology, maintaining preventive care and greater general health care to Avoid this and many other diseases. Nursing care in bacterial meningitis is mainly based on the assessment of the patient and its evolution throughout the days hospitalized, applying actions in favor of covering the needs that the patient requires for improvement. The implementation of an ECP is feasible because there is thus excellent and quality care by the nursing staff, so based on the functional patterns affected, an ECP was developed for the patient. The patient's family agreed to hospitalization so that he could receive the treatment and expressed his willingness to collaborate with the improvement of the situation, with the applied treatment the patient's situation was improved, hand in hand with the support of his family; Stay under follow-up and perform recommendations.